2017
DOI: 10.1016/j.rbmo.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial investigating the use of a predictive nomogram for the selection of the FSH starting dose in IVF/ICSI cycles

Abstract: The number of oocytes retrieved is a relevant intermediate outcome in women undergoing IVF/intracytoplasmic sperm injection (ICSI). This trial compared the efficiency of the selection of the FSH starting dose according to a nomogram based on multiple biomarkers (age, day 3 FSH, anti-Müllerian hormone) versus an age-based strategy. The primary outcome measure was the proportion of women with an optimal number of retrieved oocytes defined as 8-14. At their first IVF/ICSI cycle, 191 patients underwent a long gona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
58
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 42 publications
5
58
2
Order By: Relevance
“…Previously, a nomogram based on age, AMH and day 3 FSH was proposed to predict the FSH starting dose before an agonist protocol (La Marca et al, 2012), but this only explained 30% of the variability in ovarian sensitivity (r = 0.31). Nevertheless, a randomized trial of the use of this nomogram for agonist protocols allowed an optimal response of 63% to be obtained versus 42% in the control group (Allegra et al, 2017). In our study, even if the combination of parameters allowed a significant increase in the correlation coefficient, it remained relatively low (r = 0.6), suggesting that other parameters were involved.…”
Section: Discussioncontrasting
confidence: 49%
“…Previously, a nomogram based on age, AMH and day 3 FSH was proposed to predict the FSH starting dose before an agonist protocol (La Marca et al, 2012), but this only explained 30% of the variability in ovarian sensitivity (r = 0.31). Nevertheless, a randomized trial of the use of this nomogram for agonist protocols allowed an optimal response of 63% to be obtained versus 42% in the control group (Allegra et al, 2017). In our study, even if the combination of parameters allowed a significant increase in the correlation coefficient, it remained relatively low (r = 0.6), suggesting that other parameters were involved.…”
Section: Discussioncontrasting
confidence: 49%
“…The absence of an international AMH standard and the lack of awareness among some clinicians regarding differences in assay performance have also contributed to these concerns . For example, the algorithm developed by La Marca and colleagues for the individualization of follitropin alpha doses was initially derived using the Beckman Coulter AMH assay, but was subsequently externally validated and assessed in a randomized controlled trial using the modified AMH Generation II assay from Beckman. In contrast, follitropin delta dosing has been linked with the Roche Elecsys ® AMH immunoassay as the companion diagnostic that was validated in the phase 3 ESTHER‐1 registration study .…”
Section: Discussionmentioning
confidence: 99%
“…Several algorithms incorporating biomarkers of ovarian reserve have been developed to individualize dosing of different gonadotropin preparations . Two of these, which incorporate anti‐Müllerian hormone (AMH) concentrations as a biomarker of ovarian reserve, have been externally validated in randomized controlled clinical trials …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Nevertheless, a randomized trial of the use of this nomogram for agonist protocols allowed an optimal response of 63% to be obtained versus 42% in the control group. 16 For collection of ≥ 4 oocytes, we found a cut-off of 0.25 (AUC-0.921) for ORPI and 35 (AUC-0.952) for MORPI. Similarly, Oliveira et al, found a cut-off value of 0.2 (AUC-0.91) for ORPI.…”
mentioning
confidence: 70%